Slow strengthening of Latvia’s resilience in preventing and combating corruption: an analysis of causes - Khoma, Nataliia; Vdovychyn, Ihor (Przegląd Wschodnioeuropejski, 2023)
The aim of the article is to present the authors’ assessment of the effectiveness of the anti-corruption policy in Latvia, to establish the compliance of national anti-corruption strategies with the EU goals in terms of preventing and combating corruption. The research methods aim at confirming a hypothesis that in order to deepen anti-corruption reforms and strengthen resilience in the fight against corruption, it is not enough for Latvia to conduct only institutional reforms, but it is important to promote anti-corruption values. The study is based on the methodology of new institutionalism and axiological analysis. The authors argue that if the role of non-democratic values is significant, it will slow down the progressive institutional reforms needed to bring Latvia’s anti-corruption policies fully in line with EU development strategies.